2012
DOI: 10.1371/journal.pone.0044586
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unilateral Adrenalectomy on Transformation of Adrenal Medullary Chromaffin Cells In Vivo: A Potential Mechanism of Asthma Pathogenesis

Abstract: BackgroundDecreased epinephrine (EPI) is an important underlying factor of bronchoconstriction in asthma. Exogenous β2-adrenergic receptor agonist is one of the preferred options to treat asthma. We previously showed that this phenomenon involved adrenal medullary chromaffin cell (AMCC) transformation to a neuron phenotype. However, the underlying molecular mechanism is not fully understood. To further explore this, an asthmatic model with unilateral adrenalectomy was established in this study.Methodology/Prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
3
10
0
1
Order By: Relevance
“…In addition, OVA exposure dramatically elevated airway responsiveness even at low antigen concentration (16). In this study, we observed a significant increase in the infiltration of peribronchial inflammatory cells, particularly the lymphocytes in HiTr-treated rats.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, OVA exposure dramatically elevated airway responsiveness even at low antigen concentration (16). In this study, we observed a significant increase in the infiltration of peribronchial inflammatory cells, particularly the lymphocytes in HiTr-treated rats.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, MoTr could upregulate EPI and CORT levels. This could explain the occurrence of airway hyperresponsiveness among endurance athletes after competitions because the blunted sympathoadrenal system is unable to release sufficient EPI to dilate the bronchus (12,16,33) after prolonged high-intensity training. The time required for rats to reach exhaustion was used to evaluate the efficacy of different training regimens in inducing exercise tolerance.…”
Section: L608 Adrenal Medulla Cells Conversion In Eibmentioning
confidence: 99%
“…The ultrathin tissue sections (50 nm) were stained with uranyl acetate and lead citrate, and finally examined under a H-7,500 transmission electron microscope (Hitachi, Tokyo, Japan). The densities of chromaffin granules per gland (/mm 3 ) were assessed for every rat (Hu et al 2012a). The numbers of neurite-bearing cells and AMCCs in the adrenal medulla of individual rats were counted and the percentages of neurite-bearing cells in the total numbers of cells were calculated, based on at least thirty cells from two sections of each sample and 4-5 rats per group.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…Our previous studies have shown that adrenal medullary chromaffin cells (AMCCs) have a tendency to transform into neurons, which results in impaired endocrine function of the adrenal medulla, thereby leading to a decrease in the levels of circulating epinephrine in a rat model of asthma (Feng and Hu 2005;Feng et al 2012;Hu et al 2012a). In addition, we found that high-intensity exercise not only promoted inflammatory responses and increased the airway resistance, but also induced neuronal transdifferentiation of AMCCs and subsequently decreased the levels of circulating epinephrine while moderate-intensity of exercise reversed these changes (He et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Дисбаланс в экспрессии этих рецепторов в гладкой мускулатуре дыхательных путей может играть роль в патогенезе БА. Отмечено, что у больных БА сни жен уровень эндогенного адреналина, чем объясня ется его высокая эффективность, связанная с введе нием экзогенного адреналина при БА [23]. Кроме того, при активации β2 адренорецепторов ингибиру ется функция различных воспалительных клеток, участвующих в патогенезе БА, в т. ч. тормозится IgE опосредованное высвобождение гистамина [24], овальбумин индуцированная инфильтрация эози нофилами дыхательных путей и адгезия эозинофи лов на фибробластах легких, продукция IL 4 и IL 13 Т клетками человека [25].…”
Section: обзорыunclassified